L’angelo triste di Wim Wenders. Innocenza, tempo, kairos - Pio Colonnello (Rivista di Estetica, 2024)
Wim Wenders’ films offer not only emotions but are also a source of profound reflections on human existence, on the meaning of the change that breaks into the actuality of existence, on the privilege that mankind has to enjoy even the small pleasures of life. This essay deals with some central themes present in The Wings of Desire (Der Himmel über Berlin), with emphasis on the literary, conceptual and poietic references, which are a sort of “subtext”, a “secret plot” for the understanding of the film.